Hubungan Body Shaming Dengan Kepercayaan Diri Pada Remaja Karang Taruna Desa Dompilan di Sukoharjo - agustin, mellani (Fakultas Sosial Humaniora dan Seni Usahid Surakarta, 2023)
The body is one of the parts that is often seen from a person, because it is the part that is seen so that an assessment of the ideal body standard appears as a comparison. The phenomenon of ideal body standards sometimes requires a person to follow or change their appearance in accordance with the ideal standards that have been determined or desired by the community. The population in this study were Youth Youth Organizations in Dompilan Village. A sample of 16 Karang Taruna youths used a purposive sampling technique. The characteristics of the sample determined are adolescents who have an ideal body such as too fat and too thin, male and female adolescents who are in the Karang Taruna Organization of Dompilan Village